Cold plasma jet with dielectric barrier configuration: Investigating its effect on the cell membrane of E. coli and S. cerevisiae and its impact on the quality of chokeberry juice. (January 2021) - Gan, Zhilin; Feng, Xiaoru; Hou, Yanan; Sun, Aidong; Wang, Ruixue
Abstract: Here, we investigated the effects of cold plasma (CP), a nonthermal processing technology, on Escherichia coli and Saccharomyces cerevisiae inactivation and the quality of chokeberry juice (CJ). A CP jet with a dielectric barrier configuration was used to process the CJ, and the inactivation of E. coli and S. cerevisiae was evaluated using microscopy and propidium iodide staining. Microbial inactivation increased with treatment time and decreased with sample volume, and E. coli was inactivated to a greater extent than S. cerevisiae . The CP sterilization effect is possibly due to CP-generated active particles, such as reactive oxygen species, which attack microbial cell membranes and intracellular components leading to cell rupture. Relative to control juice, CP did not affect titratable acid, soluble reducing sugar, and soluble solid percentage values. Moreover, CP was superior to thermal treatment (90 °C for 15 s) given the improved anthocyanin, phenol, and vitamin C content, reduced color change, and enhanced antioxidant capacity of the processed CJ. Therefore, CP may be a promising method for CJ juice processing. Highlights: Cold plasma treatment inhibited growth of E. coli and S. cerevisiae in chokeberry juice. The inactivation effect of cold plasma on E. coli and S. cerevisiae was due to the damage of cell membrane. Cerevisae was the more resistant microorganism compared to E. coli under cold plasma treatment. Compared with thermal processing, cold plasma could better keep the original quality of chokeberry juice.